Proceedings of the 21st International Seminar on Paste and Thickened Tailings 2018
DOI: 10.36487/acg_rep/1805_21_reid
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical effects of polymer treatment on tailings – state of knowledge review

Abstract: As the trialling and application of polymer treatment of tailings at the point of discharge has increased, so have studies to assess the effects of polymer treatment on subsequent tailings geotechnical behaviour. A review of the publically available studies is presented, including laboratory and in situ tests on mature fine tailings, comparison of consolidation tests on a range of tailings types, and a large comparative study on a synthetic tailings that included laboratory and cone penetrometer testing. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…However, it is noted that as part of their SD preparation process, Chang et al (2011) added a flocculant to the tailings to enable looser densities to be achieved. This then raises important questions about the applicability of the results to an unflocculated thickened tailings, as there is clear evidence that addition of flocculants to slurry-prepared specimens is likely to affect both mechanical properties and potentially the CSL (Mao & Fahey 1999;Reid & Fourie 2016, 2018a, 2018b. Further study of these aspects would be useful, as if flocculants can be used to achieve looser states while creating a specimen representative of in situ, this would be a major advantage for tailings laboratory testing works.…”
Section: Other Examples Of Sd In Literaturementioning
confidence: 99%
“…However, it is noted that as part of their SD preparation process, Chang et al (2011) added a flocculant to the tailings to enable looser densities to be achieved. This then raises important questions about the applicability of the results to an unflocculated thickened tailings, as there is clear evidence that addition of flocculants to slurry-prepared specimens is likely to affect both mechanical properties and potentially the CSL (Mao & Fahey 1999;Reid & Fourie 2016, 2018a, 2018b. Further study of these aspects would be useful, as if flocculants can be used to achieve looser states while creating a specimen representative of in situ, this would be a major advantage for tailings laboratory testing works.…”
Section: Other Examples Of Sd In Literaturementioning
confidence: 99%
“…The stability and robustness of the IL-treated solid phase, in comparison to the polymer-treatments previously reported, is a crucial difference, since in the latter, when the treated sample is exposed to high stirring, the flocs formed by polymers are broken and the sample exhibits behavior closer to the untreated material. 51 Vacuum filtration, although still in initial development, has been used as an option for tailings disposal by several oil sands companies, 21 and hence was the third strategy we explored to separate the water from treated MFT. 100 g MFT was poured into a 250-mL beaker and mixed with different amounts of [C 8 NH 3 ][Oleate] following the mixing protocol described for centrifugation and gravity tests (i.e., using an overhead stirrer, 12 min, 500 rpm; see experimental section for details).…”
Section: Selection Of Ilmentioning
confidence: 99%
“…Owing to the increased application of forms of PT, studies to characterise the effects PT may have on post-deposition geotechnical behaviour of the treated slurry have been undertaken. Broadly, these studies have indicated the following effects of PT: lower consolidated densities at a given vertical effective stress and higher permeability at a given density (Jeeravipoolvarn et al 2009;Yao 2012;Manzotti et al 2014;Beveridge et al 2015;Gholami & Simms 2015;Reid & Boshoff 2015;Riley et al 2015;Znidarcic et al 2015;Reid & Fourie 2016, 2018aAbdulnabi et al 2022), higher undrained shear strengths at a given density (Jeeravipoolvarn et al 2009;Yao 2012;Beier et al 2013;Manzotti et al 2014;Cooling & Beveridge 2015;Gholami & Simms 2015;Reid & Fourie 2016Abdulnabi et al 2022) and higher CSL elevation (Reid & Fourie 2016), and various contrasting outcomes when examining the effects of PT on brittleness in undrained monotonic or post-cyclic shearing (Beier et al 2013;Gholami & Simms 2015;Reid & Fourie 2017) and drastically different penetrometer responses (Reid and Fourie 2018a), with a summary of recent studies provided by Reid and Fourie (2018b).…”
Section: Introductionmentioning
confidence: 99%